PENERAPAN ASAS KEHATI-HATIAN GUNA PENYALURAN PEMBIAYAAN MUDHARABAH - Rony Andre Christian Naldo; Bagus Firman Wibowo (Journal Recht (JR), 2024)
The development of sharia banking business activity practices has supported the progress of the Indonesian economy. In carrying out the practice of sharia banking business activities, sharia banks represented by the Main Directors can carry out legal actions in the form of distributing funds to customers who receive facilities, one of which is in the form of mudharabah financing. Before a sharia bank distributes mudharabah financing to prospective customers who receive the facility, the President Director applies the principle of prudence. This research discusses the application of the principle of prudence by sharia banks to distribute mudharabah financing to prospective customers who receive facilities. In this regard, this research is focused on examining the legal basis for sharia banks' obligations to apply the principle of prudence to distribute mudharabah financing to prospective customers who receive facilities, and the benefits of applying the principle of prudence for sharia banks to distribute mudharabah financing to prospective customers who receive facilities. This research is a type of normative research. The method used in this research is a normative juridical research method. This research is prescriptive analysis, using various types of data as is appropriate in legal research. The results of the research conclude that there are 2 provisions in the statutory regulations which form the legal basis for sharia banks' obligations to apply the principle of prudence for the distribution of mudharabah financing to prospective customers who receive the facilities. The application of the principle of prudence to distribute mudharabah financing to potential customers who receive facilities, produces 6 (six) benefits for sharia banks.